2016
DOI: 10.1111/jsbm.12224
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Social Responsibility That “Pays”: A Strategic Approach to CSR for SMEs

Abstract: This study adopts a strategic approach to corporate social responsibility (CSR), puts forward a model of CSR activities that enhance small and medium enterprises (SMEs) growth, and argues that by aligning CSR activities with the competitive strategy of the firm, SMEs enhance firm growth. We test this model using multinomial logistic analysis and data from a survey with 211 U.K.‐based SMEs. We find that CSR activities related to the community enhance firm growth for all SMEs, but especially for firms adopting a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
130
1
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(146 citation statements)
references
References 124 publications
(252 reference statements)
8
130
1
7
Order By: Relevance
“…This research revealed some interesting findings pertaining to small firms’ strategic choices with regards to their orientation and performance in the context of emerging economies which warrant thoughtful interpretation and discussion. Our findings re‐enforce Stoian and Gilman's () argument that strategic CSR pays for small businesses in the long run. The conclusion is drawn keeping in mind the above central argument.…”
Section: Resultssupporting
confidence: 87%
“…This research revealed some interesting findings pertaining to small firms’ strategic choices with regards to their orientation and performance in the context of emerging economies which warrant thoughtful interpretation and discussion. Our findings re‐enforce Stoian and Gilman's () argument that strategic CSR pays for small businesses in the long run. The conclusion is drawn keeping in mind the above central argument.…”
Section: Resultssupporting
confidence: 87%
“…This cluster is populated by papers adopting several methodological approaches. Some of them are defined as theoretical/predictive papers, such as Eltantawy, Fox, and Giunipero (), Herrera Madueno et al (), Hou, Liu, Fan, and Wei (), Stoian and Gilman (). The most cited among these (Eltantawy et al, ) analyses the impact of supply management ethical responsibility (SMER) on a firm's reputation and performance.…”
Section: Discussion Of Clustersmentioning
confidence: 99%
“…Its correlation to other strategic business decisions can positively influence the firm's competitiveness and credibility (and, in the case of the hospitality sector in Italy, considering CSR measures to support environmental-driven actions is a source of competitive advantage). On the opposite side, adopting environmental oriented CSR strategies is not necessarily a source of competitive advantage for UK SMEs adopting cost-leadership strategies (Stoian & Gilman, 2017). Credibility is cited as an important advantage of adopting CSR by SMEs (Chou et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Cespa and Cestone (2007) develop a model showing that although the interests of shareholders and stakeholders might be considered conflictual sometimes, CSR and the welfare of shareholders should be supported by shareholders. Stoian and Gilman (2017) Sample: the UK The social dimension of CSR leads to more significant growth then environmental CSR for SMEs.…”
Section: Financial Impact Of Csr: a Brief Literature Reviewmentioning
confidence: 99%